(untitled) (Моделювання, керування та інформаційні технології, 2019)
The research deals with the existence of the solution of the initial problem for hyperbolic equation under the multifrequency disturbances, which are described by the system of ordinary differential equations (ODE) with multipoint and integral conditions. The averaging method over fast variables is grounded and estimation of accuracy of the method which obviously depends on the small parameter was found.